Alzheimer's disease: elevated pigment epithelium-derived factor in the cerebrospinal fluid is mostly of systemic origin - Lang, Veronika Roswitha; Jarius, Sven (Journal of the neurological sciences, 2017)
Pigment-epithelium derived factor (PEDF) is a neurotrophic factor with neuroprotective, anti-tumorigenic, and anti-angiogenic effects. Elevated levels of PEDF have previously been proposed as a cerebrospinal fluid (CSF) biomarker for Alzheimer's disease. However, the origin of PEDF in CSF, i.e. whether it is derived from the brain or from the systemic circulation, and the specificity of this finding hitherto remained unclear. Here, we analyzed levels of PEDF in paired CSF and serum samples by ELISA in patients with Alzheimer's disease (AD, n=12), frontotemporal dementia (FTD, n=6), vascular dementia (n=4), bacterial meningitis (n=8), multiple sclerosis (n=32), pseudotumor cerebri (n=36), and diverse non-inflammatory neurological diseases (n=19). We established CSF/serum quotient diagrams to determine the fraction of intrathecally synthesized PEDF in CSF. We found that PEDF is significantly increased in CSF of patients with AD, FTD, and bacterial meningitis. Remarkably, PEDF concentrations were also significantly elevated in serum of patients with AD. CSF/serum quotient diagrams demonstrated that elevated PEDF concentrations in CSF of patients with AD are mostly due to elevated PEDF concentrations in serum. These findings underscore the importance of relating concentrations of proteins in CSF to their respective concentrations in serum to avoid erroneous interpretations of increased protein concentrations in lumbar CSF.